Low-velocity impact responses and failure of sandwich structure with carbon fiber composite honeycomb cores - Wang, Yan; Wei, Xingyu; Li, Zhibin; Gong, Cheng; Xue, Pengcheng; Xiong, Jian (International journal of impact engineering, 2024)
•Different damage states of CFRP honeycomb sandwich structure are revealed through low-velocity impact experiments.•A refined finite element model suitable for plain weave CFRP composite is established to accurately predict the impact response of the structure.•The energy absorption mechanism of CFRP honeycomb sandwich structure is investigated.•The impact-induced damage is characterized by industrial tomography technology (CT) without destroying the sandwich structure.•Reducing the cell side length is a better way to improve the impact resistance of CFRP honeycomb sandwich structure. The objective of this study is to examine the response and failure of honeycomb sandwich structures made of carbon fiber reinforced polymer (CFRP) composites under low-velocity impacts. Four impact tests with varying energies are performed to induce four distinct damage states in the sandwich structure: no discernible damage, damage to the top face sheet and a portion of the core, damage to the lower face sheet, and total penetration. The damage characteristics of the sandwich structures is analyzed by using industrial tomography technology (CT) without destroying them. A refined finite element model is established to further explain the deformation behavior and energy absorption mechanism of the structure, clarifying the effects of the honeycomb core's structural parameters, such as wall thickness, cell side length, and core height. To enhance the precision of simulation outcomes, a model for the onset and progression of damage in plain woven composites is incorporated into the user-defined material subroutine. The experiments and simulations demonstrate a high level of consistency in terms of peak loads, failure mode, and energy absorption. [Display omitted]